Feasibility of magnetic resonance imaging-only rectum radiotherapy with a commercial synthetic computed tomography generation solution. (July 2018) - Maspero, Matteo; Tyyger, Marcus D.; Tijssen, Rob H.N.; Seevinck, Peter R.; Intven, Martijn P.W.; van den Berg, Cornelis A.T.
Abstract: Background and purpose: Synthetic computed tomography (sCT) images enable magnetic resonance (MR)-based dose calculations. This work investigated whether a commercially available sCT generation solution was suitable for accurate dose calculations and position verification on patients with rectal cancer. Material and methods: For twenty rectal cancer patients computed tomography (CT) images were rigidly registered to sCT images. Clinical volumetric modulated arc therapy plans were recalculated on registered CT and sCT images. Dose deviations were determined through gamma and voxelwise analysis. The impact on position verification was investigated by identifying differences in translations and rotation between cone-beam CT (CBCT) to CT and CBCT to sCT registrations. Results: Across twenty patients, within a threshold of 90% of the prescription dose, a gamma analysis (2%, 2 mm) mean pass rate of 95.2 ± 4.0% (±1 σ ) and mean dose deviation of −0.3 ± 0.2% of prescription dose were obtained. The mean difference of translations and rotations over ten patients (76 CBCTs) was <1 mm and <0.5° in all directions. In the sole posterior-anterior direction a mean systematic shift of 0.7 ± 0.6 mm was found. Conclusions: Accurate MR-based dose calculations using a commercial sCT generation method were clinically feasible for treatment of rectal cancer patients. The accuracy of position verification was clinically acceptable. However, before clinical implementation future investigations will be performed to determine the origin of the systematic shift.